Development of strategic activities for the integration of sustainable food systems in Colombian environmental policies - Buritica Casanova, Alexander; Pérez Marulanda, Lisset; Castro, Augusto (CGIAR System Organization, 2024)
In the ever-evolving landscape of sustainable development, our recent webinar, titled “Development of Strategic Activities for the Integration of Sustainable Food Systems in Colombian Environmental Policies,” emerges as a pivotal exploration in shaping Colombia’s environmental trajectory. Hosted through a collaboration between WWF and the CGIAR’s Initiative on National Policies and Strategies through the Alliance of Bioversity & CIAT, this virtual gathering brought together a diverse array of stakeholders committed to fostering coherence in the nation’s policies. Against the backdrop of Cali, Colombia being chosen as the venue for COP 16 of the Convention on Biological Diversity and ongoing discussions at COP28 in Dubai, where food systems’ role in global sustainability took center stage, this webinar gains even greater significance.